2015
DOI: 10.1002/oby.21192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serial cell passaging in the retention of fiber type and mitochondrial content in primary human myotubes

Abstract: Objective The purpose of the study was to determine the effects of passaging on retention of donor phenotypic characteristics in primary human myotubes. Methods We established primary muscle cultures and serial passaged myotubes from physically active, sedentary lean, and individuals with type 2 diabetes (T2D). We measured maximal ATP synthesis capacity (ATPmax) and resting ATP flux (ATPase) in vivo by 31P magnetic resonance spectroscopy, type-I fibers and intramyocelluar lipid (IMCL) in vastus lateralis tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…However, we show that primary muscle cells isolated from exercise-trained skeletal muscle and grown in vitro maintain greater oxidative capacity compared to untrained donors cells. Our findings are in line with previous observations demonstrating that some exercise adaptations persist in primary myotubes grown in vitro (6,7). Together, these data suggest that primary myotubes isolated from exercise-trained individuals maintain the “exercise metabolic program” for enhanced oxidative metabolism ex vivo .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, we show that primary muscle cells isolated from exercise-trained skeletal muscle and grown in vitro maintain greater oxidative capacity compared to untrained donors cells. Our findings are in line with previous observations demonstrating that some exercise adaptations persist in primary myotubes grown in vitro (6,7). Together, these data suggest that primary myotubes isolated from exercise-trained individuals maintain the “exercise metabolic program” for enhanced oxidative metabolism ex vivo .…”
Section: Discussionsupporting
confidence: 93%
“…It is worth noting that all of our experiments were carried out at passage four. Prior work has shown that the metabolic characteristics of myotubes gradually fade after each passage (7,19). Thus, it would be of use to identify how many passages the “exercise metabolic program” can persist in these myotubes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, imprinting of muscle satellite cells appears to be relatively stable, and it can persist in vitro across many passages of cells (Covington et al . 2015; Gaster, 2019). Seaborne et al .…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a very limited number of studies have explored the impact of relatively short term in vivo interventions on the in vitro phenotypes of cultured muscle cells (Sparks et al 2013;Hinkley et al 2017;Lund et al 2017). Importantly, imprinting of muscle satellite cells appears to be relatively stable, and it can persist in vitro across many passages of cells (Covington et al 2015;Gaster, 2019). Seaborne et al (2018a,b) showed that even acute exercise-induced changes in methylation of specific genes related to exercise adaptive response can persist in skeletal muscle for as long as 22 weeks.…”
Section: Metabolic Dysfunction Persists In Cultured Myotubes From Patients With Iimmentioning
confidence: 99%